(untitled) (International Journal of Innovative Technologies in Economy, 2020)
In practice, a systematic approach is needed that allows you to combine the assessment and further changes in marketing activities. Such an approach should take into account the adoption of managerial decisions regarding improving the efficiency of marketing based on a system of assessment indicators, both marketing activities and the business as a whole, and provide for a program of coordinated changes in business and marketing, which allows to improve these indicators. taking into account the characteristics of the external environment and the resource potential of the enterprise. The result of using this approach is a more efficient state of marketing and business systems, ensuring their interconnection and coordination, taking into account market conditions. The development and implementation of a systematic approach contributes to the application of the theory and methodology of change management in the context of increasing the effectiveness of marketing activities.